A home automation architecture based on LoRa technology and Message Queue Telemetry Transfer protocol. (October 2018) - Gambi, Ennio; Montanini, Laura; Pigini, Danny; Ciattaglia, Gianluca; Spinsante, Susanna
In recent years, Internet of Things technologies gained momentum in various application areas, including the Smart Home field. In this view, the smart objects available in the house can communicate with each other and with the outside world by adopting solutions already proposed for Internet of Things. In fact, among the challenges to face during the design and implementation of an Internet of Things–based Smart Home infrastructure, battery usage represents a key point for the realization of an efficient solution. In this context, the communication technology chosen plays a fundamental role, since transmission is generally the most energy demanding task, and Internet of Things communication technologies are designed to reduce as much as possible the power consumption. This article describes an Internet of Things–oriented architecture for the Smart Home, based on the long-range and low-power technology LoRa. Moreover, in order to enable the devices to communicate with each other and the outside world, the Message Queue Telemetry Transfer protocol is used as a domotic middleware. We show that LoRa, designed by having in mind the typical requirements of Internet of Things (i.e. low power consumption, sporadic transmission, and robustness to interference), is well-suited to also meet the need of more established home automation systems, specifically the low latency in message delivery. Interoperability among different devices may also be obtained through the Message Queue Telemetry Transfer midlleware.